Tax compliance: when do employees behave like the self-employed? - Besim, M; Jenkins, GP (Routledge Taylor & Francis Ltd, 2005)
Previous studies of the underreporting of income for tax purposes have used private employees as the benchmark to which other groups' compliance was measured. In this paper it is suggested that there are a number of circumstances when there will be an incentive for private employees and their employers to collude to understate employee wages and salaries for purposes of taxation. The existence of high marginal tax rates of income tax combined with high social security payroll taxes are the typical conditions that stimulate this behaviour. These conditions are present in North Cyprus. This paper examines a rich source of household consumption expenditure and income data for North Cyprus that allows one to separate out the consumption expenditures made by the self-employed, private employees and civil servants over specific periods of time. From the comparison of consumption expenditures on food by these three groups it is possible to estimate how much self-employed and the private employees understated their incomes as compared to the civil servants. It is found that in North Cyprus private employees understate their incomes by approximately the same proportion of their incomes as do the self-employed.